Tainted : how philosophy of science can expose bad science - Shrader-Frechette, K. S. (Kristin Sharon) (Environmental ethics and science policy., 2014)
This is the first book on practical philosophy of science and how to practically evaluate scientific findings that have life-and-death consequences. Showing how to uncover scores of scientific flaws -- typically used by special interests who try to justify their deadly pollution -- this book aims to liberate the many potential victims of environmentally-induced disease and death.